The Physiatry Workforce in 2019 and Beyond, Part 2: Modeling Results. (4th September 2021) - Dall, Timothy M.; Reynolds, Ryan L.; Chakrabarti, Ritashree; Forte, Gaetano J.; Langelier, Margaret; Wang, Shen; Whyte, John; Sridhara Ankam, Nethra; Annaswamy, Thiru M.; Fredericson, Michael; Jain, Nitin B.; Perret Karimi, Danielle; et al.
Abstract : Objective: The aim of this study was to assess the current and future adequacy of physiatrist supply in the United States. Design: A 2019 online survey of board-certified physiatrists ( n = 616 completed, 30.1% response) collected information about demographics, practice characteristics, hours worked, and retirement intentions. Microsimulation models projected future physiatrist supply and demand using data from the American Board of Physical Medicine and Rehabilitation, national and state population projections, American Community Survey, Behavioral Risk Factor Surveillance System, Medical Expenditure Panel Survey, and other sources. Results: Approximately 37% of 8853 active physiatrists indicate that their workload exceeds capacity, 59% indicate that workload is at capacity, and 4% indicate under capacity. These findings suggest a national shortfall of 940 (10.6%) physiatrists in 2017, with substantial geographic variation in supply adequacy. Projected growth in physiatrist supply from 2017 to 2030 approximately equals demand growth (2250 vs. 2390), suggesting that without changes in care delivery, the shortfall of physiatrists will persist, with a 1080 (9.7%) physiatrist shortfall in 2030. Conclusion: Without an increase in physiatry residency positions, the current national shortfall of physiatrists is projected to persist. Although a projected increase in physiatrists' use of advanced practice providers may help preserve access to comprehensive physiatry care, it is not expected to eliminate the shortfall.